2006
DOI: 10.1111/j.1474-9726.2006.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymic output and functionality of the IL‐7/IL‐7 receptor system in centenarians: implications for the neolymphogenesis at the limit of human life

Abstract: SummaryDuring aging, the thymus undergoes a marked involution that is responsible for profound changes in the T-cell compartment. To investigate the capacity of the thymus to produce new cells at the limit of human lifespan, we analyzed some basic mechanisms responsible for the renewal and maintenance of peripheral T lymphocytes in 44 centenarians. Thymic functionality was analyzed by the quantification of cells presenting the T-cell receptor rearrangement excision circles (TREC). A new method based upon real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 58 publications
9
81
0
Order By: Relevance
“…The intrathymic supplementation of IL-7 in mice also failed to increase RTE during aging (40). Furthermore, a recent study in 44 centenarians noted the presence of TREC-bearing cells in the periphery, but no difference in IL-7 or IL-7 receptor-α mRNA could be detected in elderly compared with young and middle-aged individuals, suggesting a limited role for IL-7 alone in strategies for thymic renewal in aging (44). A number of studies have shown that activation of somatotropic axis and ablation of gonadal steroids promote thymic rejuvenation (24)(25)(26)(27)30), clearly suggesting the resilient nature of the thymus and its capacity for renewal.…”
Section: Figurementioning
confidence: 99%
“…The intrathymic supplementation of IL-7 in mice also failed to increase RTE during aging (40). Furthermore, a recent study in 44 centenarians noted the presence of TREC-bearing cells in the periphery, but no difference in IL-7 or IL-7 receptor-α mRNA could be detected in elderly compared with young and middle-aged individuals, suggesting a limited role for IL-7 alone in strategies for thymic renewal in aging (44). A number of studies have shown that activation of somatotropic axis and ablation of gonadal steroids promote thymic rejuvenation (24)(25)(26)(27)30), clearly suggesting the resilient nature of the thymus and its capacity for renewal.…”
Section: Figurementioning
confidence: 99%
“…The phenotypic features of centenarians, as far as the percentages of na€ ıve (CD45RA1, CCR71, defined T N ), central memory (CD45RA2, CCR71, defined T CM ), effector memory (CD45RA2, CCR72, defined T EM ), and terminally differentiated (CD45RA1, CCR72, defined T EMRA ) T cells are concerned, have been previously described in details (13). The donors included in this study had almost identical T cell differentiation patterns of those above quoted (13).…”
Section: Strategy For the Identification Of The Subpopulations Presenmentioning
confidence: 99%
“…The donors included in this study had almost identical T cell differentiation patterns of those above quoted (13). Data regarding the fine identification of the T cell populations were processed as shown in Figure 1.…”
Section: Strategy For the Identification Of The Subpopulations Presenmentioning
confidence: 99%
“…Particularly, phenotypic analysis confirmed that the exhaustion of thymic output with age is at the basis of the deficient replacing of naïve T cells lost in the periphery and results in the inability to maintain the breadth of the T cell repertoire. Recently, the presence of TCR rearrangement excision circles (TREC+) cells in very few naïve T lymphocytes in centenarians has been demonstrated, suggesting that in such long-living subjects, these cells could either derive from residues of thymic lymphopoietic islets or even represent long-living lymphocytes that have not yet encountered their antigen [8] . Indeed, data in humans suggest that the replacement of thymic parenchyma with adipose tissue is a discontinuous process, reaching a maximum at around 50 years of age and not progressing further thereafter [9] .…”
Section: Changes In Adaptive Immunitymentioning
confidence: 99%